Development of a Control System and Functional Validation of a Parallel Robot for Lower Limb Rehabilitation - Pisla, Doina; Nadas, Iuliu; Tucan, Paul; Albert, Stefan; Carbone, Giuseppe; Antal, Tiberiu; Banica, Alexandru; Gherman, Bogdan (Actuators, 2021)
This paper is focused on the development of a control system, implemented on a parallel robot designed for the lower limb rehabilitation of bedridden stroke survivors. The paper presents the RECOVER robotic system kinematics, further implemented into the control system, which is described in terms of architecture and functionality. Through a battery of experimental tests, achieved in laboratory conditions using eight healthy subjects, the feasibility and functionality of the proposed robotic system have been validated, and the overall performance of the control system has been studied. The range of motion of each targeted joint has been recorded using a commercially available external sensor system. The kinematic parameters, namely the patient’s joints velocities and accelerations have been recorded and compared to the ones obtained using the virtual model, yielding a very small difference between them, which provides a validation of the RECOVER initial design, both in terms of mechanical construction and control system.